Reconfigurable Full Color Display using Anisotropic Black Phosphorus. Issue 16 (21st May 2021) - Jia, Jingyuan; Ban, Yu; Liu, Kuan; Mao, Libang; Su, Ying; Lian, Meng; Cao, Tun
Abstract: Next‐generation color display entails miniaturization, reconfigurablity, flexibility, integration, and excellent workability. Recently, emerging 2D van der Waals materials offer a new opportunity to satisfy these requirements and attract intense attention, owing to their intrinsic in‐plane anisotropy for polarization dependent photosensitivity, straightforward integration with complicated nanostructures, and efficient quantum confinement for good photodetecting performances. Nevertheless, reconfigurable color display in the visible region based on the 2D material stays elusive. Black phosphorus (BP) is a newly rising member of 2D family with intense optical anisotropy. Herein, the anisotropic BP crystals are explored as an optical dielectric for the visible spectrum, which possesses a polarization‐dependent complex refractive index. A considerably large anisotropic ratio of BP enables polarized color displaying. It is experimentally and theoretically observed that the color from an air/BP/SiO2 multi‐layered Fabry–Pérot cavity reversibly changes with the polarization angle, taking advantage of polarization‐dependent complex refractive index of BP. The strategy offers a new prospect for developing next‐generation polarization‐dependent devices in data storage, anti‐counterfeiting technologies, and color display. Abstract : A new promising technique for reconfigurable color display in the visible region based on black phosphorus (BP) is proposed. Utilizing the in‐plane anisotropy of BP, such polarization sensitive device easily presents vivid colors by reversibly changing the incident polarization angle. This echoes with emerging demands from practical applications to exploit new and practical mechanisms of color display technique.